Home care for heart failure: can caregiver education prevent hospital admissions? A randomized trial in primary care. Issue 1 (January 2019) - Padula, Maria S.; D'Ambrosio, Gaetano G.; Tocci, Marina; D'Amico, Roberto; Banchelli, Federico; Angeli, Letizia; Scarpa, Marina; Capelli, Oreste; Cricelli, Claudio; Boriani, Giuseppe
Abstract : Aim: To assess the feasibility and effectiveness of a low-complexity, low-cost model of caregiver education in primary care, targeted to reduce hospitalizations of heart failure patients. Methods: A cluster-randomized, controlled, open trial was proposed to general practitioners, who were invited to identify patients with heart failure, exclusively managed at home and continuously attended by a caregiver. Participating general practitioners were then randomized to: usual treatment; caregiver education (educational session for recognizing early symptoms/signs of heart failure, with recording in a diary of a series of patient parameters, including body weight, blood pressure, heart rate). The patients were observed at baseline and during a 12-month follow-up. Results: Three hundred and thirteen patients were enrolled (163 in the intervention, 150 in the usual care group), 63% women, mean age 85.3 ± 7.7 years. At the end of the 12-month follow-up, a trend towards a lower incidence of hospitalizations was observed in the intervention group (hazard ratio 0.73; 95% CI 0.53–1.01 P = 0.061). Subgroup analysis showed that for patients with persistent/permanent atrial fibrillation, age less than 90 years or Barthel score equal to or greater than 50 a significant lower hospital admission rate occurred in the intervention group (hazard ratio 0.63; 95% CI 0.39–0.99; P = 0.048, hazard ratio 0.66; 95% CI 0.45–0.97; P = 0.036 and hazard ratio 0.61; 95% CI 0.41–0.89; P = 0.011, respectively). Conclusion: Caregivers training for early recognition of symptoms/signs of worsening heart failure may be effective in reducing hospitalizations, although the benefit was evident only in specific patient subgroups (with persistent/permanent atrial fibrillation, age <90 years or Barthel score ≥ 50), with only a positive trend in the whole cohort. Trial registration: ClinicalTrials.gov Identifier: NCT03389841. Abstract : Supplemental Digital Content is available in the text